Desde la maqama hasta el auto sacramental: la obra temprana de José Penso de la Vega. - DAVIDI, EINAT (Bulletin of Hispanic Studies (1475-3839), 2022)
This article discusses two early Hebrew works of José Penso de la Vega – the maqama Fábulas de animales (1668) and the autosacramental drama, Prisioneros de la esperanza (1673). The article focuses on the genre traditions in which the works were written, as well as on their poetic elements. The transition from the first work to the second epitomizes the emergence of Penso's unique Baroque allegorical perspective, expressed in later texts. On the poetological level, this transition amounts to an allegorization, validation and exaggeration of an interreligious polemic. The transition from prosaic elaboration of a Talmudic legend to a dramatic allegorical conflict is analysed not only as a moral message or an abstraction of the story, but also as a ('psychomachic') internalization of this polemic. Thus Penso's early work exemplifies the processes of allegorization as a transition from historical, external conflict into mental drama, which facilitates additional observations regarding psychomachich poetics.